Folk prayer as a part of stereotypic behavior in Persian linguistic culture - СОПІЛЬНЯК, С. (Київський національний університет імені Тараса Шевченка, 2022)
The speech genre of prayer as a component of stereotypical behavior of Persian linguistic culture bearers on the basis of Persian folk omens and superstitions is considered. The historiography of stereotypes, in particular communicative-behavioral stereotypes in modern linguistics, is briefly presented. The concept of speech genre is characterized. According to M. Bakhtin's definition, any human communication is based on certain speech genres, which are often stereotyped. Since the speech genre is the most important category of discourse, the classification of discourses by I. S. Shevchenko and O. I. Morozova is represented. Researchers distinguish the following subtypes of discourse within the socio-situational parameter: political, administrative, legal, military, religious, medical, business, advertising, pedagogical, sports, scientific, electronic (Internet discourse), and media varieties. Ritual type of discourse, which is relevant within the scope of the study, was also added to this typology. The speech genre of Persian folk prayer, verbalized by the words "do'ā" / "verd", is described, since it is folk, not traditional religious prayer in the context of Persian folk omens and superstitions to be a component of stereotypic behavior of Iranians and to perform primarily psychological, phatic and suggestive functions. It is determined that folk prayer in Persian linguistic culture functions not only as an act of saying a certain text to the God or the saints, but also as a talisman or amulet. Traditionally, such talismans are made in the form of texts or sayings from the Qur'an, written on a piece of paper, leather, cloth or metal. People attach these to clothing or simply carry with themselves. The central element of Persian folk prayer is a request. It has been found that there is a number of stereotypes in Persian linguo-mentality associated with images of prayer, which in turn affect the behavior of native speakers in different life circumstances. Analysis of Persian omens and superstitions on the basis of modern fiction has indicated that prayer is associated primarily with the need for protection, satisfaction of needs and hope in the minds of Iranians. It is noted that the appeal of native speakers of the Persian language and culture to folk prayer in certain situations is accompanied by a number of stereotypic ritual and semiotic actions, which demonstrates a combination of religious and magical aspects in their minds. It is stated that the specificity of the Persian speech genre of prayer is in the fact it simultaneously belongs to two types of discourse – religious and ritual.

Розглянуто мовленнєвий жанр молитви як компонент стереотипної поведінки носіїв перської лінгвокультури на матеріалі перських народних прикмет і забобонів. Стисло подано історію вивчення стереотипів, зокрема комунікативно-поведінкових стереотипів у сучасній лінгвістиці. Висвітлено поняття мовленнєвого жанру. За визначенням М. М. Бахтіна, будь-яка комунікація людини будується на основі певних мовленнєвих жанрів, які дуже часто є стереотипізованими. З огляду на те, що мовленнєвий жанр є найважливішою категорією дискурсу, наведено класифікацію дискурсів І. С. Шевченка та О. І. Морозової. У межах соціально-ситуативного параметра дослідники виділяють такі підтипи дискурсу: політичний, адміністративний, юридичний, військовий, релігійний, медичний, діловий, рекламний, педагогічний, спортивний, науковий, електронний (інтернет-дискурс), медійний різновиди. Також до цієї типології було додано ритуальний тип дискурсу, який є актуальним у межах дослідження. Охарактеризовано мовленнєвий жанр перської народної молитви, вербалізований словами "do'ā" / "verd", оскільки саме народна, а не релігійна у традиційному розумінні молитва в контексті перських народних прикмет і забобонів є складником стереотипної поведінки іранців, виконуючи передусім психологічну і фатично-сугестивну функції. Визначено, що народна молитва в перській лінгвокультурі функціонує не лише у вигляді акту промовляння певного тексту до Бога чи святих, а й як талісман чи оберіг. Традиційно такі обереги виготовляють у вигляді текстів чи висловів із Корану, написаних на шматку паперу, шкіри, тканини, металу, і прикріплюють до одягу чи просто носять із собою. Центральним елементом перської народної молитви є прохання. З'ясовано, що в перській лінгвоментальності існує багато стереотипних уявлень, пов'язаних з образами молитви, які впливають на поведінку носіїв мови за різних життєвих обставин. Аналіз перських прикмет і забобонів на матеріалі сучасної художньої літератури показав, що у свідомості іранців молитва асоціюється передусім із необхідністю захисту, задоволення потреби та надією. Зауважено, що звертання носіїв перської мови й культури до народної молитви у певних ситуаціях супроводжується багатьма стереотипними ритуально-семіотичними діями, що демонструє поєднання релігійного та магічного аспектів у їхній свідомості. Констатовано, що специфіка перського мовленнєвого жанру молитви полягає в тому, що він водночас належить до двох типів дискурсу: релігійного й ритуального.
Народна молитва як складова стереотипної поведінки в перській лінгвокультурі
Keywords: мовленнєвий жанр; дискурс; молитва; стереотип; перські прикмети й забобони; speech genre; discourse; prayer; stereotype; Persian omens and superstitions